1986
DOI: 10.1037/0003-066x.41.5.535
|View full text |Cite
|
Sign up to set email alerts
|

An occupational analysis of counseling psychology: How special is the specialty?

Abstract: The specialty of counseling psychology has come under scrutiny as a result of recent preoccupation with licensing, credentialing, and third-party payments. A lack of clarity concerning the nature of the specialization appears to be shared by psychology in general counseling psychology in particular, and also the general public. In the present study an occupational analysis of counseling psychology was conducted to determine what counseling psychologists actually do, how they feel about it, and how (if at all) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
169
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 9 publications
12
169
2
Order By: Relevance
“…The students initially had misgivings toward and limited interest in providing career interventions. Similar perceptions of career counseling have been reported by others (Fitzgerald & Osipow, 1986;Gelso et al, 1985;Pinkney & Jacobs, 1985). Students' attitudes seemed related to their assumptions about the value of career counseling or their anxieties concerning their career interventions skills.…”
supporting
confidence: 70%
“…The students initially had misgivings toward and limited interest in providing career interventions. Similar perceptions of career counseling have been reported by others (Fitzgerald & Osipow, 1986;Gelso et al, 1985;Pinkney & Jacobs, 1985). Students' attitudes seemed related to their assumptions about the value of career counseling or their anxieties concerning their career interventions skills.…”
supporting
confidence: 70%
“…The researchers have asked, in different ways, "How special are the specialties?" They have uniformly answered, "Not very" (Fitzgerald & Osipow, 1986). Some studies on the roles and functions of clinical and counseling psychologists do substantiate traditional differences, but the sim- ilarities are far more numerous (Brems & Johnson, 1997;Fitzgerald & Osipow, 1986;Norcross, Karg, & Prochaska, 1997a, 1997bWatkins, Lopez, Campbell, & Himmell, 1986).…”
Section: Professional Activitiesmentioning
confidence: 94%
“…Recent national data (American Psychological Association, 2010;2009a) (Yamamoto, 1963) and 80% in the mid-1980's (Fitzgerald, & Osipow, 1986;Munley, Pate, & Duncan, 2008). In sum, these data stress the minimal presence of scholarship around the experiences of men in the field given the combined shifts in gender composition and proliferation of multiculturalism.…”
Section: The Place Of Men In Psychologymentioning
confidence: 99%
“…Recent data and counseling psychology doctoral students (American Psychological Association, 2010). These statistics juxtapose clearly against data from 1973, which revealed that men comprised nearly 80% of psychology, Ph.D. recipients in the workforce -a percentage that shrank to 50% by 2006 (Hart, 2009 (Fitzgerald, & Osipow, 1986;Munley, Pate, & Duncan, 2008). While the increased representation of women is an encouraging change within the field (Pion et al), this gender shift also naturally seeks explanation for fewer male students seeking and completing psychology doctoral degrees.…”
Section: Further Rationale For Study Of Male Psychology Students and Grcmentioning
confidence: 99%